STUDENTS’ ERRORS IN SOLVING PISA QUESTIONS ON SPACE AND SHAPE CONTENT - Rachma Kiraam; Duano Sapta Nusantara; Feri Tiona Pasaribu (Jurnal Numeracy, 2025)
The main objective of this study is to identify and explain students’ errors in solving PISA questions on Space and Shape content using Newman’s Error Analysis. The errors analyzed include five categories: reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. This study employs a descriptive qualitative approach with data collected through tests and interviews. The research subjects are ninth-grade students at SMP Negeri 7 Muaro Jambi. The results show that students frequently made errors in the stages of understanding the questions, modelling the questions into mathematical forms, and process skills. These errors were by weaknesses in processing information, limited mathematical skills in real-life contexts, and a lack of experience in practicing PISA questions. These findings highlight the importance of familiarizing students with contextual problems as an effort to minimize errors in solving PISA questions.